Impact of N‐Truncated Aβ Peptides on Cu‐ and Cu(Aβ)‐Generated ROS: CuI Matters!. Issue 5 (14th December 2020) - Esmieu, Charlène; Ferrand, Guillaume; Borghesani, Valentina; Hureau, Christelle
Abstract: In vitro Cu(Aβ1– x )‐induced ROS production has been extensively studied. Conversely, the ability of N ‐truncated isoforms of Aβ to alter the Cu‐induced ROS production has been overlooked, even though they are main constituents of amyloid plaques found in the human brain. N ‐Truncated peptides at the positions 4 and 11 (Aβ4– x and Aβ11– x ) contain an amino‐terminal copper and nickel (ATCUN) binding motif (H2 N‐Xxx‐Zzz‐His) that confer them different coordination sites and higher affinities for Cu II compared to the Aβ1– x peptide. It has further been proposed that the role of Aβ4– x peptide is to quench Cu II toxicity in the brain. However, the role of Cu I coordination has not been investigated to date. In contrast to Cu II, Cu I coordination is expected to be the same for N ‐truncated and N ‐intact peptides. Herein, we report in‐depth characterizations and ROS production studies of Cu (Cu I and Cu II ) complexes of the Aβ4–16 and Aβ11–16 N ‐truncated peptides. Our findings show that the N ‐truncated peptides do produce ROS when Cu I is present in the medium, albeit to a lesser extent than the unmodified counterpart. In addition, when used as competitor ligands (i.e., in the presence of Aβ1–16 ), the N ‐truncated peptides are not able to fully preclude Cu(Aβ1–16 )‐induced ROS production. Abstract : Truncated but important : The ability of N‐truncated amyloid‐β peptides to either contribute to or prevent the production of deleterious reactive oxygen species by Cu or Cu(amyloid‐β) is examined, and evidence for the key role of copper(I) is presented.